Graphical user interface for bounded-addition fuzzy splicing systems and their variants / Mathuri Selvarajoo ... [et al.] - Selvarajoo, Mathuri; Santono, Mohd Pawiro; Fong, Wan Heng; Sarmin, Nor Haniza (Universiti Teknologi MARA Press (Penerbit UiTM), 2023)
A splicing system is one of the early theoretical proposals of the DNA-based computation device. The splicing operation starts when two DNA molecules are cut at specific subsequences with the presence of restriction enzymes: the first part is then connected to the second part of the other molecule, or vice versa, to produce splicing languages. Fuzzy with bounded-addition operation has been introduced as a restriction in splicing systems to increase the generative power of the languages generated. In this research, a graphical user interface is developed to generate all the splicing languages generated by bounded-addition fuzzy splicing systems and their variants. An algorithm is developed using JAVA and Visual Studio Code software in order to replace the time-consuming manual computation of the languages generated by bounded-addition fuzzy DNA splicing systems and their variants.